2009
DOI: 10.1520/jai102032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Hygrothermal Analysis to Uncertainty in Rain Data

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The uncertainty of rainfall data in this study should also be noted, which is highly relevant as the effect of rainfall data on hygrothermal performance can have a significant effect on simulated mould growth. Cornick et al [55] found that there was uncertainty associated with the use of 6 h precipitation times steps, as utilised by the NCEI archive. It has been demonstrated that measuring rainfall data in hourly timesteps may not even be granular enough and may still produce errors in wind-driven rain [56].…”
Section: Outdoor Climate and Orientationmentioning
confidence: 99%
“…The uncertainty of rainfall data in this study should also be noted, which is highly relevant as the effect of rainfall data on hygrothermal performance can have a significant effect on simulated mould growth. Cornick et al [55] found that there was uncertainty associated with the use of 6 h precipitation times steps, as utilised by the NCEI archive. It has been demonstrated that measuring rainfall data in hourly timesteps may not even be granular enough and may still produce errors in wind-driven rain [56].…”
Section: Outdoor Climate and Orientationmentioning
confidence: 99%